The Knowledge that construct the quilombola Identity in the media:An archeogenealogical discoursive analysis (PERcursos Linguísticos, 2020)
This article discusses the knowledge that construct identity for the quilombola subject in the media. To this focus, we mobilize different statements, produced by distinct subjects, which are: three statements from the newspaper “O Estado do Maranhão”; three videos hosted on YouTube; and three excepts of interviews that we made with residents from three quilombola communities in Maranhão. The theoretical-methodological approach is the discourse analysis, centered in Michel Foucault’s archeogenealogy, which understand the genealogy as a instance in which are confronted the scientific knowledge (that enjoys social recognition) and the dominated knowledge (considered as lesser knowledge in view of the claim to truth of the scientific knowledge), and the archeology as a method of analyzing local discourse (FOUCAULT, 2013). We conclude that the journalist knowledge present on the printed media that we analyzed is anchored in scientific knowledge, such as that of historiography, sociology, archeology and the law, to talk about the quilombola, but not in the dominated knowledge of the inhabitants of a quilombola community.